2021
DOI: 10.1002/adfm.202106264
|View full text |Cite
|
Sign up to set email alerts
|

Finite‐Temperature Dynamics in Cesium Lead Iodide Halide Perovskite

Abstract: Lattice dynamics are often regarded as signatures of the underlying crystal structure. Here, a first‐principle‐based effective Hamiltonian method combined with molecular dynamics simulations is used to study dynamical behaviors of CsPbI3 perovskite across temperature and structural phase transitions. A single (short‐range tilting) parameter in this effective Hamiltonian is varied in order to make the temperature range of the intermediate tetragonal P4/mbm phase, existing in‐between the cubic Pmtrue3¯m and orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(67 reference statements)
1
1
0
Order By: Relevance
“…(b) The model system is not too small to exhibit disorder. (c) There are several previous DFT-based studies of these alloy series that can serve as references to this work. ,, Previous DFT-based studies of Cs-based pure perovskites (such as CsPbI 3 and CsPbBr 3 ) indicated that the α and β phases are essentially dynamical mixtures of disordered structures. In this paper, we tackle this issue beyond pure compounds by constructing the phase diagrams for alloys. Contribution from the lattice (phonon) vibrations was taken into account for this purpose.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…(b) The model system is not too small to exhibit disorder. (c) There are several previous DFT-based studies of these alloy series that can serve as references to this work. ,, Previous DFT-based studies of Cs-based pure perovskites (such as CsPbI 3 and CsPbBr 3 ) indicated that the α and β phases are essentially dynamical mixtures of disordered structures. In this paper, we tackle this issue beyond pure compounds by constructing the phase diagrams for alloys. Contribution from the lattice (phonon) vibrations was taken into account for this purpose.…”
Section: Introductionsupporting
confidence: 83%
“…Actually, the nature of the cubic phase of Cs-based perovskites is unclear. Previous computational studies indicate that it is a dynamical mixture of highly disordered tilted structures , but not the untilted ones as used in this work. In addition, we admit that our phase diagram can only give quantitative information, mostly because the phonon calculations with harmonic approximations are not precise enough.…”
Section: Results and Discussionmentioning
confidence: 99%